Prophylactic laser in age-related macular degeneration: the past, the present and the future. (May 2018) - Findlay, Quan; Jobling, Andrew; Vessey, Kirstan; Greferath, Ursula; Phipps, Joanna; Guymer, Robyn; Fletcher, Erica
Abstract The presence of drusen in the posterior eye is a hallmark feature of the early stages of age-related macular degeneration and their size is an indicator of risk of progression to vision-threatening forms of the disease. Since the initial observations that laser treatment can resolve drusen, there has been great interest in whether laser treatment can be used to reduce the progression of age-related macular degeneration. In this article, we review the development of lasers for the treatment of those with age-related macular degeneration. We provide an overview of the clinical trial results that demonstrated drusen resolution but that had mixed effects on progression of disease. In addition, we provide a summary of the recent developments in pulsed lasers that are designed to reduce the energy applied to the posterior eye to provide the therapeutic effects of conventional continuous wave lasers while reducing the secondary tissue effects.